AGRICULTURAL RELATIONS BETWEEN MOROCCO AND THE EUROPEAN UNION - Llaga, Israel Macias (European Scientific Journal, ESJ, 2013)
The relations between Morocco and the European Union rotate, especially from the Moroccan side, around one single desire: The creation of a Free Trade Zone (FTZ). From the first EU-Morocco Euro-Mediterranean Association Agreement (1996) until the new Agreement on Agriculture (2010), through the granting of Advanced Status to Morocco (2008), most agricultural and industrial products enjoyed certain privileges, financial advantages and finally their practical liberalisation on the EU market. This research will focus on the analytical study of the Institutional Framework to develop relations between the EU and Morocco on agriculture. In this sense, we will analyze: Firstly, the legal framework that legally and politically regulates these relations, i.e. the Treaty on European Union (1992) and the European Neighbourhood Policy (2004); secondly, the agreements that have had the greatest impact on agricultural development in Morocco.